ChemInform Abstract: A Versatile Synthesis of β‐Lactam‐Fused Oxacycles Through the Palladium‐Catalyzed Chemo‐, Regio‐, and Diastereoselective Cyclization of Allenic Diols. Issue 25 (5th June 2015) - Alcaide, Benito; Almendros, Pedro; Carrascosa, Rocio; Casarrubios, Luis; Soriano, Elena
Abstract: β‐Lactam‐fused morpholine, oxocines and dioxonines are formed chemo‐ and regioselectively from allenic diols by palladium catalysis.